Implementation of State Social Policy in the Sphere of State Financial Guarantees of Public Health Services - Корнілова, Олеся Володимирівна; Корнілова, О. В.; Корнилова, Олеся Владимировна; Kornilova, Olesia V.; Наньєва, Марія Іванівна; Наньєва, М. І.; Наньева, Мария Ивановна; Nanieva, Mariia I.; Nanieva, Maria; Пожарова, Оксана Вікторівна; Пожарова, О. В.; Пожарова, Оксана Викторовна; et al. (Universidade Federal da Paraíba, 2020)
The article is devoted to a detailed analysis of the implementation of the state social policy in the sphere of state financial guarantees of public medical services and the activity of the National Health Service of Ukraine, its main purposes and functions. Amendment proposals to improve national legislation in the sphere of healthcare are being formulated. Problems of standards and warranties in the sphere of healthcare are also investigated in the article, because health is a top priority for both the citizen and the nation as a whole. The problems of financial guarantees of public health services have been analyzed, eventually the healthcare sector remained unattended for a quite a long time, despite the constant integration processes, implementation of international legal acts into national legislation. The results that are currently being achieved thanks to the ongoing medical reform show a number of unresolved issues and inconsistencies in the area of financial guarantees for public health services, but for example, the system "money follow a client" is gradually becoming a generally accepted fact that has only a positive effect not only for economy, but also in medicine sphere.

Стаття присвячена детальному аналізу реалізації державної соціальної політики у сфері державних фінансових гарантій державних медичних послуг та діяльності Національної служби охорони здоров'я України, її основних цілей та функцій. Формулюються пропозиції щодо внесення змін до національного законодавства у сфері охорони здоров’я. У статті також досліджуються проблеми стандартів та гарантій у сфері охорони здоров’я, оскільки здоров’я є пріоритетом як для громадянина, так і для нації в цілому. Проаналізовано проблеми фінансових гарантій державних служб охорони здоров'я, враховуючи що сектор охорони здоров'я залишався поза увагою досить тривалий час, незважаючи на постійні інтеграційні процеси, імплементацію міжнародно-правових актів у національне законодавство. Результати, які в даний час досягаються завдяки медичній реформі, що триває, свідчать про низку невирішених питань та невідповідностей у сфері фінансових гарантій для охорони здоров’я, але, наприклад, система «гроші йдуть за клієнтом» поступово сприймається загальновизнаним фактом, що має лише позитивний ефект не лише для економіки, а й для медицини.

Статья посвящена детальному анализу реализации государственной социальной политики в сфере государственных финансовых гарантий государственных медицинских услуг и деятельности Национальной службы здравоохранения Украины, ее основных целей и функций. Формулируются предложения по внесению изменений в национальное законодательство в сфере здравоохранения. В статье также исследуются проблемы стандартов и гарантий в сфере здравоохранения, поскольку здоровье является приоритетом как для гражданина, так и для нации в целом. Проанализированы проблемы финансовых гарантий государственных служб здравоохранения, учитывая то, что сектор здравоохранения оставался без внимания довольно длительное время, несмотря на постоянные интеграционные процессы, имплементацию международно-правовых актов в национальное законодательство. Результаты, которые в настоящее время достигаются благодаря медицинской реформе, которая продолжается, свидетельствуют о ряде нерешенных вопросов и несоответствий в сфере финансовых гарантий для здравоохранения, но, например, система «деньги следуют за клиентом» постепенно воспринимается общепризнанным фактом, что имеет лишь положительный эффект не только для экономики, но и для медицины.
Kornilova O. Implementation of State Social Policy in the Sphere of State Financial Guarantees of Public Health Services / O. Kornilova, M. Nanieva, O. Pozharova, R. Pidlypna, M. Kovach // Gênero & Direito. – V. 9 (04). – Universidade Federal da Paraíba, 2020. – P. 240-255.
Keywords: state social policy; medical care; health care; primary care; financial guarantees; державна соціальна політика; медичне обслуговування; охорона здоров’я; первинна медична допомога; фінансові гарантії; государственная социальная политика; медицинское обслуживание; здравоохранение; первичная медицинская помощь; финансовые гарантии; Research Subject Categories::LAW/JURISPRUDENCE; Research Subject Categories::MEDICINE::Social medicine::Public health medicine research areas